Odpowiedź :
[tex]A) \ 0,3\cdot(\frac{2}{5}-\frac{1}{3})=\frac{3}{10}\cdot(\frac{6}{15}-\frac{5}{15})=\frac{3}{10}\cdot\frac{1}{15} = \frac{1}{10}\cdot\frac{1}{5} = \frac{1}{50}=0,02\\\\\\G) \ (2\frac{2}{3}-0,6)\cdot0,25-\frac{1}{4} = (\frac{8}{3}-\frac{6}{10})\cdot\frac{25}{100}-\frac{1}{4} = (\frac{8}{3}-\frac{3}{5})\cdot\frac{1}{4}-\frac{1}{4} = (\frac{40}{15}-\frac{9}{15})\cdot\frac{1}{4}-\frac{1}{4}=\\\\=\frac{31}{15}\cdot\frac{1}{4}-\frac{1}{4} = \frac{31}{60} -\frac{15}{60} = \frac{16}{60}=\frac{4}{15}[/tex]
[tex]a)0,3*(\frac{2}{5}-\frac{1}{3})=0,3*(\frac{6}{15}-\frac{5}{15})=\frac{3}{10}*\frac{1}{15}=\frac{1}{10}*\frac{1}{5}=\frac{1}{50}[/tex]
[tex]g)(2\frac{2}{3}-0,6)*0,25-\frac{1}{4}=(2\frac{2}{3}-\frac{3}{5})*\frac{1}{4}-\frac{1}{4}=(2\frac{10}{15}-\frac{9}{15})*\frac{1}{4}-\frac{1}{4}=2\frac{1}{15}*\frac{1}{4}-\frac{1}{4}=\frac{31}{15}*\frac{1}{4}-\frac{1}{4}=\frac{31}{60}-\frac{15}{60}=\frac{16}{60}=\frac{4}{15}[/tex]